Long non-coding RNA expression profiling in the lungs of pulmonary arterial hypertension rats with acute inflammation. (November 2019) - Yang, Yue; Cao, Yanan; Qin, Gang; Wang, Lu; Li, Qian; Dai, Sisi; Guo, Lizhe; Guo, Qulian; Peng, Yong Gang; Duan, Bin; Wang, E.
Background: We performed RNA-sequencing to investigate the changes and expression profiles in long non-coding RNAs (lncRNAs) and their potential functional roles in the lungs of pulmonary arterial hypertension rats responding to acute inflammation. Methods: To establish a pulmonary arterial hypertension rat model, monocrotaline was injected intraperitoneally and lipopolysaccharide was given to induce acute inflammation. Selected lncRNAs were validated by quantitative real-time polymerase chain reaction (qRT-PCR). Bioinformatics analyses were carried out to predict the potential biological roles of key lncRNAs. Results: Twenty-eight lncRNAs and seven mRNAs with elevated expression and 202 lncRNAs and 36 mRNAs with decreased expression were found in the lung tissues of lipopolysaccharide-treated pulmonary arterial hypertension rats compared with control group. The qRT-PCR validation results were consistent with the bioinformatics analysis. Gene ontology analyses showed that the mRNAs and lncRNAs were differentially expressed in different pathways regarding biological process, cellular components, and molecular function. The functions of differentially expressed messenger RNAs (DEmRNAs) and DElncRNAs were indicated by Kyoto Encyclopedia of Genes and Genomes enrichment. Conclusion: The DEmRNAs co-expressed with DElncRNAs were obviously enriched in inflammation. DElncRNAs and DEmRNAs in the lungs of pulmonary arterial hypertension rats changed with acute inflammation may provide new insights into the pathogenesis of pulmonary arterial hypertension.